Upaya Peningkatan Aktivitas Belajar dan Kemampuan Berpikir Kritis Peserta Didik Melalui Model Discovery Learning pada Materi Kesetimbangan Kimia - Tantri, Ristamulia; Holiwarni, Betty; Albeta, Sri Wilda (Program Studi Pendidikan Kimia, FKIP, Universitas Riau, 2025)
This study aims to improve learning activities and critical thinking skills of students by implementing the discovery learning model. This type of research is classroom action research. Data collection was carried out in January 2025. The sample in this study were 36 students of class XI 1 SMAN 6 Pekanbaru. The instruments used were observation sheets of student and teacher activities, evaluation questions and test questions at the end of each cycle based on critical thinking indicators. The results of the study showed that student learning activities increased from cycle I by 56.94%, including the sufficient category, and in cycle II by 71.48%, including the good category, and critical thinking skills increased from cycle I by 55.56% to 94.44% in cycle II.